Poetic Approach in Drama Script Study: Analysing Willy Loman’s Disappointments in Arthur Miller's Death of a Salesman in Teaching English as a Foreign Language Context - Seli, Sastika (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
This article describes and explains how Culler’s (1997) poetics in the study of literature can be used to gain literary competency for the teaching of literature in an English as a foreign language (EFL) environment. The use of this strategy is discussed using one of the most famous play scripts in American literature: Arthur Miller's Death of a Salesman. Following Culler's poetics technique, the study focuses on one of the themes present in the play script: Willy Loman's (the main character) disappointments, which make up the majority of the story with a dramatic ending: Willy's decision to commit suicide. This article seeks to persuade EFL teachers who study literature to take Culler's side and use poetics as the beginning point for a literature study in order to increase their students’ literary ability.